Implementation of Continuous Review System Method, Periodic Review System Method and Min-Max Method for Cheese Powder Inventory (Case Study: PT. Mayora Indah TBK) - Muhammad Kholil; Indra Almahdy; Annisa Fortinina; Adizty Suparno (International Journal of Advanced Technology, 2020)
PT. Sejahtera Mitra Lestari is a company engaged in manufacturing industrial chemicals specifically for the rubber industry. The irregular placement of finished products in the storage can cause errors in the delivery of goods due to good management for delivering goods with a relatively fast time. The effort to overcome this problem is through designing of warehouse layout with the Class-Based Storage method. Grouping based on popularity. Stages of research carried out by calculating the warehouse, the frequency of displacement, the number of storage places, the displacement distance. Improvements begin by sorting material based on frequency and variations of three classes, namely A, B, C. To design the layout, information is needed when making a new storage layout. The results showed that the layout of the optimal results could reduce the displacement distance by 17.19% in 6 months and allow space to be 73.91%.